2007
DOI: 10.1016/j.jmb.2007.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution of a Tagged Chimeric Gammaretrovirus: Identification of Novel cis-Acting Elements that Modulate Splicing

Abstract: SummaryRetroviruses are well known for their ability to incorporate envelope proteins from other retroviral strains and genera and even from other virus families. This characteristic has been widely exploited for the generation of replication-defective retroviral vectors, including those derived from murine leukemia virus (MLV), bearing heterologous envelope proteins. We desired to investigate the possibility of "genetically" pseudotyping replication-competent MLV by replacing the native env gene in a full-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…MLV must maintain a balance between its full-length genomic transcript and spliced env transcript to undergo productive replication. We previously found that MLV is highly sensitive to modifications to its genome that perturb normal splicing of the viral transcript and that attenuation of replication can serve as a useful indicator of aberrant splicing (23). In stark contrast to the results obtained with the 5Ј ss-depleted dicistronic constructs, the proviruses containing the eIF4G, NRF, Rbm3, and XIAP sequences produced exceedingly high levels of GFP upon transfection (Fig.…”
Section: Six Putative Cellular Iress Exhibit Little Activity In a Dicmentioning
confidence: 81%
See 1 more Smart Citation
“…MLV must maintain a balance between its full-length genomic transcript and spliced env transcript to undergo productive replication. We previously found that MLV is highly sensitive to modifications to its genome that perturb normal splicing of the viral transcript and that attenuation of replication can serve as a useful indicator of aberrant splicing (23). In stark contrast to the results obtained with the 5Ј ss-depleted dicistronic constructs, the proviruses containing the eIF4G, NRF, Rbm3, and XIAP sequences produced exceedingly high levels of GFP upon transfection (Fig.…”
Section: Six Putative Cellular Iress Exhibit Little Activity In a Dicmentioning
confidence: 81%
“…As an approach to producing such mutations, we serially passaged the viruses containing these IRESs to evolve mutants in which the splice sites had been inactivated through natural selection. We previously used this method to isolate rapidly replicating mutants of a retrovirus that had been crippled by an oversplicing defect (23). From five passaged isolates of the NRF and Rbm3 viruses, we identified three unique mutants, each of which possessed a single or double point mutation at or adjacent to the IRES 3Ј ss (SI Fig.…”
Section: Six Putative Cellular Iress Exhibit Little Activity In a Dicmentioning
confidence: 99%
“…The pAZE-GFP plasmid is a biologically active clone obtained from the laboratory of Christopher Logg [50]. It contains LTRs and gagpol derived from Moloney murine leukemia virus and an envelope gene derived from amphotropic MLV.…”
Section: Methodsmentioning
confidence: 99%
“…The alloCTL were generated by one-way MLTR according to methods previously published 9 . Effector alloCTL were harvested 4-5 days after one-way MLTR and transduced with RRV-GS4-EMD (Figures 3 and 5) or RRV-ACE-EMD (Figure 6) 10,11 . Higher transduction levels were achieved with the GS4 vector utilizing a Gibbon ape leukemia virus envelope than with the amphotropic ACE vector.…”
Section: Discussionmentioning
confidence: 99%
“…We also used transduction with viral vectors encoding for fluorescent proteins as an additional way to visualize the cells. For certain assays, we transduced the alloCTL with retroviral replicating vectors (RRV) coding for Emerald Green (EMD) fluorescent protein 10,11 ; for others, tumor cells were transduced with lentiviral vectors coding for mStrawberry.…”
Section: Introductionmentioning
confidence: 99%